Influence of family social capital on career calling: moderated mediation effect of family socioeconomic status - Wenjie Yang; Xiaomin Su (Humanities & Social Sciences Communications)
Abstract With the rapid advancement of science and technology and the profound restructuring of economic structures, a plethora of new occupational types are emerging. Concurrently, individual career attitudes and preferences are evolving, showcasing a more diverse and flexible characteristic. The career orientation of the new generation of employees emphasizes adapting to changes and paying more attention to pursuing a career development path that matches their personal interests and values. In this context, career calling highlights individuals’ deep concern for the meaning of work and personal development. Calling encourages individuals to bravely face the complex and changing professional environment, inspiring their internal drive to realize their self-worth and contribute to society. While the outcomes of career calling have been widely discussed in current academic discourse, the factors influencing its formation and development and operational mechanisms require further investigation. This study selected 550 senior interns from three universities in the eastern, central, and western regions of Guangdong Province, China, as research participants. The findings indicate: 1. Family social capital has a significant positive influence on career calling. 2. Family social capital significantly influences career calling through occupational self-efficacy. 3. Family socioeconomic status not only positively moderates the relationship between family social capital and occupational self-efficacy, but also positively moderates the influence of family social capital on career calling through occupational self-efficacy. Simultaneously, it also provides crucial theoretical support for higher education institutions and social policymakers to develop more precise and effective career development strategies and intervention measures, thereby cultivating a more significant number of individuals with career calling for the benefit of society and businesses.